2018
DOI: 10.1111/apce.12206
|View full text |Cite
|
Sign up to set email alerts
|

Why Farmers Involve Themselves in Co‐operative District Councils

Abstract: This study finds that selective incentives induce district council members and chairpersons to work for the collective best of a co-operative membership. Being the lowest echelon of a co-operative's internal governance hierarchy, district councils constitute a link between the membership and the board of directors. Previous research indicates that district council members are often driven by a co-operative conviction and social concerns. The present study challenges this view. On the basis of a survey of all 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 25 publications
1
23
1
Order By: Relevance
“…However, no study has focused specifically on the relationship between social networks and members' willingness to be elected representatives. The present study adds to the strand of research on farmers' behavior in relation to their agricultural cooperatives, and specifically to the literature on why members are motivated to engage themselves in cooperatives (Arcas‐Lario et al, 2014; Barraud‐Didier, Henninger, & Akremi, 2012; Hakelius & Hansson, 2016a, 2016b; Morfi, Nilsson, & Österberg, 2018).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…However, no study has focused specifically on the relationship between social networks and members' willingness to be elected representatives. The present study adds to the strand of research on farmers' behavior in relation to their agricultural cooperatives, and specifically to the literature on why members are motivated to engage themselves in cooperatives (Arcas‐Lario et al, 2014; Barraud‐Didier, Henninger, & Akremi, 2012; Hakelius & Hansson, 2016a, 2016b; Morfi, Nilsson, & Österberg, 2018).…”
Section: Introductionmentioning
confidence: 85%
“…In their study of district council members of a Swedish forestry cooperative, Kronholm and Wästerlund (2013, p. 426) have found that members' involvement is “primarily founded on values and tradition, which implies that replenishment occurs primarily from the traditional types of forest owners.” In an investigation of district council members in a Swedish agricultural cooperative, Morfi et al (2018) have found that members involve themselves for individualistic reasons, but these motivational factors are linked to the fact that the members act within a social context. This is the case with factors, such as the fulfillment of norms, access to information, personal development, traditions, a sense of a cooperative community, and status, as well as appreciation by fellow farmers.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences in research findings in cooperatives may be due to the conception of members of a cooperative. While some cooperatives are business-oriented, with the members' shares being tradable on the market, harsh market conditions encourage them to continue in the cooperative, but creating a more individualistic posture (Morfi et al, 2018). Other cooperatives, such as Veiling Holambra, are more focused on the common good of the members, increasing their bargaining power and allowing them to benefit from modern value chains (Hao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%